L' origine du Sanctus - Kate, Albert ten (Ephemerides theologicae Lovanienses, 2007)
Until now, the research on the origin of the Sanctus, a liturgical hymn, has been found in the quotation of Isaiah 6,3, where the prophet says a thrice "holy!". But in the oldest testimony of this book, 1Q Is a, there is only a twofold exclamation of "holy!". Usually this has been hold for a mistake of the copiist, but there are far more signs that the twofold exclamation is the original and that the threefold came only by influence of Christianity. As there were much more occurences in Qumran liturgical practices, they all intend to make a superlative: "most holy" would then be the best translation. Later on, Christianity with its Trinitarian dogma influenced the liturgical practices to a threefold exclamation. In our article we will pass on the different prooftexts in the context of Early Christianity.